Genetic differentiation between captive and wild populations induced by selective breeding in morphologically diverse Takifugu pufferfish - Nobuhisa Kajino; Hyoun-Joong Kim; Hyun-Ki Hong; Wan-Ok Lee; Hiroshi Takahashi; Kwang-Sik Choi; Hyung-Bae Jeon (Frontiers in Marine Science)
Pufferfish from the genus Takifugu are vital commercial resources in East Asia. Within the genus, the taxonomic status of two commercially important species, T. rubripes and T. chinensis, remains ambiguous, especially given their morphological variability. Recent observations of suspected hybrids between T. rubripes and T. chinensis on Jeju Island, South Korea, displaying intermediate phenotypes, have further confused their classification. In this study, we analyzed 73 pufferfish, including wild-caught T. rubripes, T. chinensis, suspected hybrids, and farm-bred T. rubripes, using 16 microsatellite loci to explore their population structure and evolutionary relationships. The Bayesian clustering and principal coordinate analysis showed minimal genetic differentiation among the wild populations, regardless of phenotype. This finding suggests that T. rubripes and T. chinensis might represent a single species with considerable morphological diversity. In contrast, farm-bred T. rubripes exhibited significant genetic differentiation from wild populations, likely due to domestication-induced genetic drift. These results challenge the existing taxonomic distinctions between T. rubripes and T. chinensis and highlight the profound impact of aquaculture on the genetics of captive populations. This study underscores the necessity for ongoing research into the taxonomy and population genetics of the T. rubripes-chinensis complex to guide conservation and management strategies and stresses the importance of genetic monitoring in pufferfish aquaculture to counteract inbreeding and genetic drift.